Evaluation of hypoxia markers in critically ill patients categorized by their burden of organ dysfunction: a novel approach to detect pathophysiological and clinical relevance in a secondary analysis of a prospective observational study - Centner, Franz-Simon; Brohm, Kathrin; Mindt, Sonani; Jäger, Evelyn; Hahn, Bianka; Fuderer, Tanja; Lindner, Holger A.; Schneider-Lindner, Verena; Krebs, Jörg; Neumaier, Michael; Thiel, Manfred; Schöttler, Jochen (International journal of molecular sciences, 2025)
In critically ill patients, compromised microcirculation causes tissue hypoxia, organ failure, and death. These pathophysiological processes occur particularly in patients with high illness severity, so reliable hypoxia biomarkers should reflect this in their occurrence. This secondary analysis of a prospective study categorized patients by their burden of organ dysfunction (BOD) using the cohort’s median initial sequential organ failure assessment (SOFA) score of 8 as a cutoff. The kinetic parameters of the hypoxia markers lactate and S-adenosylhomocysteine (SAH) were analyzed for correlation with organ dysfunction severity and mortality prediction. In low BOD patients, neither marker correlated with SOFA. In high BOD patients, lactate showed a moderate correlation and SAH showed a strong correlation. Lactate correlated with organ dysfunction in survivors but not in non-survivors, while SAH correlated strongly in non-survivors but not in survivors. In univariate logistic regression, lactate predicted mortality moderately in low BOD (areas under the receiver operating characteristic curves (AUROCs) 0.7-0.8) but poorly in high BOD patients (AUROCs 0.5-0.7). SAH’s prediction improved from poor to excellent (AUROCs 0.8-0.9) with higher BOD. Thus, SAH appears superior to lactate in the detection of organ dysfunction severity and mortality prediction in high BOD patients.